2019
DOI: 10.1016/j.hemonc.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathic side effect of L-asparaginase on fibrinogen level in childhood acute lymphoblastic leukemia during induction phase

Abstract: Significant reduction in fibrinogen level occurred in childhood ALL patients after treatment with L-asparaginase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In one of the previous studies, a decrease in serum albumin and increases in ALT and fatty liver were observed in hepatic imaging of patients after LA utilization 8,9 . In addition, LA was shown to reduce fibrinogen's hepatic synthesis, which illustrates its coagulopathic adverse effects 10 …”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In one of the previous studies, a decrease in serum albumin and increases in ALT and fatty liver were observed in hepatic imaging of patients after LA utilization 8,9 . In addition, LA was shown to reduce fibrinogen's hepatic synthesis, which illustrates its coagulopathic adverse effects 10 …”
Section: Introductionmentioning
confidence: 77%
“…8,9 In addition, LA was shown to reduce fibrinogen's hepatic synthesis, which illustrates its coagulopathic adverse effects. 10 Developing natural drugs from medicinal plants to hepatic function stimulation, enabling organ protection or hepatic cells regeneration in liver injuries, might be more effective alternative treatments with low toxicity than chemical medications. 11,12 However, the existence of biological barriers in the body, consisting of drug-metabolizing enzymes and efflux transporters, could negatively affect the efficiency and pharmacokinetic characteristics of the plant and prevent them from reaching their intended sites of action.…”
mentioning
confidence: 99%
“…Moreover, studies on patients with acute lymphatic leukemia on asparaginase treatment showed depletion of fibrinogen. 20,21…”
Section: Asns Impact On Hepatic Functionmentioning
confidence: 99%
“…ALL treatment per se is a known risk factor for thrombosis, especially asparaginase and corticosteroids 4,5 . Asparaginase affects several haemostatic proteins, leading to coagulopathies such as low antithrombin and hypofibrinogenaemia 6,7 . Thromboprophylaxis in ALL patients has been discussed over the years.…”
Section: Introductionmentioning
confidence: 99%